Perceived level of stress among nightshift working nurses in hospitals of Kathmandu city - Baniya, Ambika; Paudel, Ashok Kumar; Chhetri, Muni Raj; Thapa, Pramila (Journal of Chitwan Medical College, 2021)
Background: Nurse’s professionals experience an overwhelming level of stress due to socio-demographic and work place related factors. This cross-sectional hospital-based study was designed to assess perceived level of stress and influencing factors among nightshift working nurses in Kathmandu, Nepal. Methods: A cross-sectional hospital-based study using multistage sampling techniques among 266 randomly sampled nightshift working nurses was conducted. Perceived Stress Scale used to assess level of stress and associated factors. Self-administered Perceived Stress Scale was pretested and finalized before data collection. Data analyzed by using IBM SPSS verson-20 and relevant statistical test applied. Results: Mean age of nurses was 24.46 years ± 3.771 S.D. Most of the nurses (41.3%) were between 22-26 years and 70.9% of nurses were unmarried. Nearly eighty percent of the nurses had moderate level perceived stress followed by low level (15.5%) and high level (4.9%) stress. There is significance association between sleeping hours of the nurses and stress (p= 0.013). Conclusions: Prevalence of moderate level perceived stress was highest among nightshift working nurses in hospitals of Kathmandu, Nepal. There is significance association between sleeping hours of the nurses and stress. Longer working hours in nightshift, shorter sleeping hours, unequal and overloaded duty were main factors related to higher rates of self reported stress.